Cardiovascular outcomes and safety of SGLT2 inhibitors in chronic kidney disease patients - Chen, Xiutian; Wang, Jiali; Lin, Yongda; Yao, Kaijin; Xie, Yina; Zhou, Tianbiao (Frontiers in Endocrinology, 2023)
Background Sodium–glucose co-transporter 2 (SGLT2) inhibitors provide cardiovascular protection for patients with heart failure (HF) and type 2 diabetes mellitus (T2DM). However, there is little evidence of their application in patients with chronic kidney disease (CKD). Furthermore, there are inconsistent results from studies on their uses. Therefore, to explore the cardiovascular protective effect of SGLT2 inhibitors in the CKD patient population, we conducted a systematic review and meta-analysis to evaluate the cardiovascular effectiveness and safety of SGLT2 inhibitors in this patient population. Method We searched the PubMed® (National Library of Medicine, Bethesda, MD, USA) and Web of Science™ (Clarivate™, Philadelphia, PA, USA) databases for randomized controlled trials (RCTs) of SGLT2 inhibitors in CKD patients and built the database starting in January 2023. In accordance with our inclusion and exclusion criteria, the literature was screened, the quality of the literature was evaluated, and the data were extracted. RevMan 5.3 (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, Denmark) and Stata® 17.0 (StataCorp LP, College Station, TX, USA) were used for the statistical analyses. Hazard ratios (HRs), odds ratios (ORs), and corresponding 95% confidence intervals (CIs) were used for the analysis of the outcome indicators. Results Thirteen RCTs were included. In CKD patients, SGLT2 inhibitors reduced the risk of cardiovascular death (CVD) or hospitalization for heart failure (HHF) by 28%, CVD by 16%. and HHF by 35%. They also reduced the risk of all-cause death by 14% without increasing the risk of serious adverse effects (SAEs) and urinary tract infections (UTIs). However, they increased the risk of reproductive tract infections (RTIs). Conclusion SGLT2 inhibitors have a cardiovascular protective effect on patients with CKD, which in turn can significantly reduce the risk of CVD, HHF, and all-cause death without increasing the risk of SAEs and UTIs but increasing the risk of RTIs.